In situ measurement of an emerging persistent, mobile and toxic (PMT) substance - Melamine and related triazines in waters by diffusive gradient in thin-films. (1st November 2021) - Liu, Si-Si; Cai, Qi-si; Li, Cailin; Cheng, Shengming; Wang, Zhanyun; Yang, Yuanyuan; Ying, Guang-Guo; Sweetman, Andy J.; Chen, Chang-Er
Highlights: A MCX-DGT is developed for determining melamine and related triazines in waters. MCX-DGT sampler performs reliably and robustly in both laboratory and field. Higher level of melamine was found in effluent than influent of the sewage treatment plant, suggesting no effective removal. Melamine was at the highest reported concentration to date in the sewage treatment plant. DGT was demonstrated as a complement to grab sampling in monitoring triazines in waters. Abstract: Melamine has received increasing public attention as a persistent, mobile and toxic (PMT) substance. To better assess environmental exposure and risks of melamine and related triazines (cyromazine, ammeline, and atrazine), a new passive sampling method based on the diffusive gradients in thin films (DGT) technique has been developed and validated in this study. The studied triazines were adsorbed quickly and strongly by the selected mixed cation exchange (MCX) binding gels. This MCX-DGT can linearly accumulate these chemicals over at least 5 days, with neither significant individual influence from pH (6–8), ionic strength (0.01–0.5 M) or dissolved organic matter (0–10 M), or interaction effects. Field applications in Southern China showed that DGT performed well in both sewage treatment plant (STP) and river samples. Melamine was found to be the dominant triazine with the concentrations at μg·L −1 in the STP and receiving river. Surprisingly, much higher concentration of melanine was found in the STP effluent than influent, and appeared to be some of the highest concentrations reported in STPs worldwide to date. Comparable melamine and atrazine concentraions in the STP effluent and receiving river suggested other sources to the river. The MCX-DGT sampler developed here was demonstrated to be reliable and robust for measuring the triazines in waters, and is promising as an in situ tool in understanding the occurrence, sources, and fate of the emerging PMT substances in aquatic environment. Graphical abstract: Image, graphical abstract